Features of regional forecasting of socio-economic development in the context of post-war reconstruction of Ukraine - Lapan, Oksana; Lukin, Sergiy (Management and Entrepreneurship: Trends of Development, 2024)
The article discusses the issue of regional forecasting of socio-economic development and the disclosure of its specifics in the conditions of the post-war reconstruction of Ukraine as a result of Russian aggression. The need to study such a topic arose due to the fact that today the leadership of our country, representatives of partner countries, representatives of various national and international non-governmental organizations are paying considerable attention to planning the reconstruction of Ukraine after the war. At the same time, there is a need to understand the specifics of constructing forecasted scenarios at the regional level. The purpose of the article is to reveal the peculiarities of regional forecasting of socio-economic development in the context of the post-war reconstruction of Ukraine. Methodology: The research uses general scientific methods such as abstraction, analysis and synthesis, logical generalization and comparison, as well as the method of functional analysis of available practical quantitative and qualitative data related to the research topic. A regulatory framework has been developed that regulates issues of regional development and obliges local authorities to focus on the development of relevant plans and measures. The Recovery Plan of Ukraine and the Concept of the Strategy for the Post-War Recovery and Development of Ukraine were analyzed for the aspect of taking into account the regional factor. It was noted that forecasting the development of regions separately provides meaningful work in preparation for the development of national plans for development and recovery after the war. Results: we identified and substantiated the criteria that take into account the peculiarities of regional development forecasting, namely, the orientation of the region in the pre-war period, the focus on finding partners for strategic cooperation, and the determination of the level of casualties as a result of armed russian aggression. JEL Classification: H70, O10